METODE PERBANYAKAN Azotobacter sp. DENGAN MEDIA CAIR DI KANTOR KOORDINATOR PTPH BOJONEGORO - Nur Maulidah; Fita Fitriatul Wahidah (Jurnal Matematika dan Sains (JMS), 2021)
This study aimed to determining how the production process of Azotobacter sp. using liquid media as the biological agent of Azotobacter sp. Azotobacter sp. is a nitrogen fixing bacteria as fertilizer of soil. Azotobacter sp. including natural biological agents that are environmentally. The process production of the biological agent was used liquid media from soybean which carried out in the coordinator office of PTPH bojonegoro. The result showed that propagation of Azotobacter sp. can be done with the stages of making bacterial isolation on Natrium Agar (NA) and making liquid media with soybean (based ingredients). The calculation method using the TPC method is done by counting the number of bacterial colonies that appear on the petridish. From the results of the calculation of the TPC the average number is 3,8 x 108, showed that is feasible to be used as an effective growth regulator fertilizer.